Ischiofemoral impingement in joint preserving hip surgery: prevalence and imaging predictors - Alexander F. Heimann; Moritz Wagner; Peter Vavron; Alexander Brunner; Till D. Lerch; Ehrenfried Schmaranzer; Joseph M. Schwab; Simon D. Steppacher; Moritz Tannast; Reto Sutter; Florian Schmaranzer (Insights into Imaging)
Abstract Objectives To determine the prevalence of ischiofemoral impingement (IFI) in young patients evaluated for joint-preserving hip surgery and investigate its associations with osseous deformities and intra-articular pathologies. Methods Retrospective study of 256 hips (224 patients, mean age 34 years) that were examined with radiographs and MR arthrography for hip pain. Quadratus femoris muscle edema was used to indicate IFI and measurements of ischiofemoral space were performed. Imaging analysis assessed cam deformity, femoral torsion, neck-shaft angle, ischial angle, acetabular coverage-/ version, and chondro-labral pathology. Prevalence of MRI findings consistent with IFI was calculated and univariate- and multivariate logistic regression identified associations between IFI and hip deformities. Results Quadratus femoris muscle edema consistent with IFI was present in 9% (23/256 hips) with narrowing of the ischiofemoral distance (1.7 ± 0.6 cm vs 2.8 ± 0.7 cm in the control group, p < 0.001) and a higher prevalence in females (89% vs 45%, p < 0.001). Multiple regression identified female sex (OR 12.5, 95% CI: 1.6–98.2, p = 0.017), high femoral torsion (OR 3.9, 1.4–10.4, p = 0.008), and ischial angle > 127° (OR 5.9, 1.3–27.1, p = 0.023) as independent predictors of IFI. Labral tears were highly prevalent in both IFI and control groups (87% vs 89%, p = 0.732); cartilage lesions were less common in the IFI group (26% vs 52%, p = 0.027). Conclusion IFI was present in 9% of young patients evaluated for joint-preserving surgery, associated with female sex, high femoral torsion and increased ischial angle. The comparable prevalence of labral lesions but lower prevalence of cartilage damage suggests complex relationships between extra- and intra-articular pathologies. Critical relevance statement Recognizing IFI and its link to hip deformities and chondrolabral damage is crucial for clinicians, as it represents an important differential diagnosis, directly impacting joint-preserving treatment strategies in young adults with hip pain. Key Points The prevalence and imaging predictors of IFI in young patients remain unknown. IFI occurred in 9%, with predictors including female sex, high femoral torsion, and an increased ischial angle. IFI is an important differential diagnosis in joint-preserving hip surgery. Graphical Abstract